- #1

angel23

- 21

- 0

## Homework Statement

consider the difference equation

x(n+2)-0.3679x(n+1)+0.3679x(n)=0.3679u(n+1)+u(n)

where u(n) is the input and given by

u(n)=0 n<0

u(0)=1

u(1)=0.2142

u(2)=-0.2142

u(n)=0 n=3,4,5...

determine the output x(n)

## The Attempt at a Solution

let A=0.3679 and B=0.3642

i took z transform for both sides so it became.

z^2 x(z)-z^2x(0)-zx(1)-A[zx(z)-zx(0)]+Ax(z)=A[zu(z)-zu(0)]+Bu(z)

x(z)[z^2-Az+A]+x(0)[Az-z^2]-zx(1)=A[zu(z)-zu(0)]+Bu(z)

x(z)[z^2-Az+A]=A[zu(z)-zu(0)]+Bu(z)-x(0)[Az-z^2]+zx(1)

then what can i do?

also how can i make use of u(1)=0.2142

u(2)=-0.2142

i am too confused and need help.